Inside Front Cover: Microproteomic Profiling of High‐Grade Squamous Intraepithelial Lesion of the Cervix: Insight into Biological Mechanisms of Dysplasia and New Potential Diagnostic Markers. Issue 1 (7th February 2019) - Pottier, Charles; Kriegsmann, Mark; Alberts, Deborah; Smargiasso, Nicolas; Baiwir, Dominique; Mazzucchelli, Gabriel; Herfs, Michael; Fresnais, Margaux; Casadonte, Rita; Delvenne, Philippe; De Pauw, Edwin; Longuespée, Rémi
Abstract : High‐grade squamous intraepithelial lesion (HSIL) is a known precursor for squamous cell carcinoma of uterine cervix. Proteomic characterization of HSIL is of utmost importance to understand the biological mechanisms underlying its development and find new markers for pathology and pharmacology. Microproteomics is used to depict the proteomic landscape of HSIL and highlight interesting markers for diagnostics. This is reported by Charles Pottier, Mark Kriegsmann, Deborah Alberts, Nicolas Smargiasso, Dominique Baiwir, Gabriel Mazzucchelli, Michael Herfs, Margaux Fresnais, Rita Casadonte, Philippe Delvenne, Edwin De Pauw, Rémi Longuespée in article1800052 .